Identification of Eco-friendly Practices in the Industries of EGREE Region for Sustainable Development, Andhra Pradesh, India - Teki Surayya; Gudivada Rajendra Prasad; Arigela Srinivasa Rao; Jetti Srinivasa Ravisankar; Matcha Johar Khrisna; Indukuri Satyanarayana Raju (Universitas Andalas, 2020)
This study has been conceived with the basic objective to investigate the role played by industries in the East Godavari River Estuarine Ecosystem (EGREE) region to reduce the level of industrial pollution and other eco-friendly initiatives taken for eco-friendly and sustainable development. Effluent treatment systems prevalent in the majority of the studied industries are in working conditions. 57% of industries' effluent treatment plants are working conditions, 29% of the industries are using landing filling methods for disposal of agro-based waste. There is a strong common understanding among the EGREE region industries to lower the CO2 footprint by substituting coal consumption with bio-fuel. In some companies like ITC, biofuel consumption is 80%, and the remaining 20% is Coal. Government and policymakers have to make provision for industrial waste disposal, especially for small and medium enterprises (SME). Waste transporting cost is high for SME. Effluent treatment plant (ETP) and sewage treatment plant (STP) conditions to be verified by the pollution control board periodically